Critical thinking - Moore, Brooke Noel (McGraw-Hill, 2012)
Imagine a class where students are actively and personally engaged in thinking critically while also discovering how to apply those thinking skills in everyday life. Now imagine those same students confidently participating in class, working efficiently through the exercises outside class, and performing better in the course. With Connect Critical Thinking, students can achieve this success. Connect Critical Thinking is a first: a learning program with pedagogical tools that are anchored in research on critical thinking. Along with Moore & Parker's engaging writing style and the wealth of topical exercises and examples that are relevant to students' lives, Connect Critical Thinking helps ensure that students can come to class confident and prepared. What other course provides students with skills they can apply so broadly to success in school and success in life?